Diaporthe species occurring on Senna bicapsularis in southern China, with descriptions of two new species - Yang, Qin; Fan, Xin-Lei; Du, Zhuo; Tian, Cheng-Ming (Phytotaxa, 2017)
Diaporthe species include important plant pathogenic fungi with extensive host ranges and geographic distributions. In the present study, two new species of Diaporthe causing diebacks from southern China are described and illustrated. Isolates were characterized morphologically and assigned to species based on multigene sequence analyses. Phylogenetic analysis based on the internal transcribed spacer (ITS) region, calmodulin (CAL), histone H3 (HIS), translation elongation factor 1-alpha (TEF1-α) and beta-tubulin (TUB) region grouped isolates into two distinct lineages. Within each linage these species appear to be unique and are described as D. sennae sp. nov and D. sennicola sp. nov, and their relationships with other species in the genus are indicated.